ANALISIS KOMITMEN PIMPINAN TERHADAP PENERAPAN SISTEM MANAJEMEN K3 (SMK3) DI PT KRAKATAU STEEL (PERSERO)TBK. - Shabira Noviandini; Ekawati Ekawati; Bina Kurniawan (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2017)
RI Employment and Transmigration Minister in 2013 mentioned that at this time many managements of the company that undertook SMK3 was limited by the formality with the signing of the policy K3 so as the accident figure in the workplace was still high. The management commitment had the influence was biggest towards the application SMK3. The commitment was the strong determination that pushed someone to carry him out. PT Krakatau Steel (Persero) Tbk. was the iron industry and the biggest steel in South-East Asia that had the potential for the high danger from the hot explanation, the explanation of dust, radiation to the explanation of metal vapour. This research aimed at analysing the management commitment towards the application SMK3 in PT Krakatau Steel (Persero) Tbk. This research was the qualitative research descriptive with the deep interview. The subject of this research numbering 1 person as the main informant and 2 people as the triangulation informant. Results of the research showed the form of the management commitment in the matter of resources from the availability of the Expert K3 as well as the team of the evacuation, communication in the form of safety induction and safety briefing, the involvement in the training that regarding K3, and the appointment of the personnel that had responsibility as well as the expertise in accordance with his field. PT Krakatau Steel (Persero) Tbk must carry out the repeated survey towards the policy in accordance with the change that happened in the work field.